2017
DOI: 10.1002/jssc.201601076
|View full text |Cite
|
Sign up to set email alerts
|

Liquid chromatography with tandem mass spectrometry method for the determination of nicotine and minor tobacco alkaloids in electronic cigarette refill liquids and second-hand generated aerosol

Abstract: A liquid chromatography with tandem mass spectrometry method for the simultaneous quantification of nicotine and seven minor tobacco alkaloids in both refill liquids for electronic cigarettes and their generated aerosol was developed and validated. The limit of detection and limit of quantification values were 0.3-20.0 and 1.0-31.8 ng/mL, respectively. Within-laboratory reproducibility was 8.2-14.2% at limit of quantification values and 4.8-12.7% at other concentration levels. Interday recovery was 75.8-116.4%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 35 publications
1
30
0
Order By: Relevance
“…While nicotine delivery appears to be comparable or higher in TS (Famele et al, 2017; Margham et al, 2016), other studies point to poor quality control in e-cigarette production such that reported nicotine levels range from 45 to 131% of stated label concentration (Peace et al, 2016). While the suppression of CBF immediately post-exposure from both types of sources is suggestive of epithelial patho-physiology, it is noteworthy that although the advertised chemical constituents contained in e-cigarettes are substan-tively limited relative to the many well-documented toxic components present in TS, the post-exposure pattern of suppression of CBF by EV exposure was similar to that of TS.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…While nicotine delivery appears to be comparable or higher in TS (Famele et al, 2017; Margham et al, 2016), other studies point to poor quality control in e-cigarette production such that reported nicotine levels range from 45 to 131% of stated label concentration (Peace et al, 2016). While the suppression of CBF immediately post-exposure from both types of sources is suggestive of epithelial patho-physiology, it is noteworthy that although the advertised chemical constituents contained in e-cigarettes are substan-tively limited relative to the many well-documented toxic components present in TS, the post-exposure pattern of suppression of CBF by EV exposure was similar to that of TS.…”
Section: Discussionmentioning
confidence: 98%
“…Different approaches to the chemical analysis of TS and EV and to the assessment of nicotine delivery concentration (Famele et al, 2017; Margham et al, 2016; Oh & Kacker, 2014; Peace et al, 2016) have confounded simple comparisons. While nicotine delivery appears to be comparable or higher in TS (Famele et al, 2017; Margham et al, 2016), other studies point to poor quality control in e-cigarette production such that reported nicotine levels range from 45 to 131% of stated label concentration (Peace et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…ysis of the effects of the ENDS components (PG/VG and nicotine). We analyzed all e-liquids using a LiChrospher 5-μm RP-select B 60-Å, LC column 125 × 4 mm on an Agilent 1200 HPLC for nicotine-associated contaminants, as these are often the most common impurities found among e-liquids (56,57). We were unable to detect toxic contaminants, such as anabasine (Supplemental Figure 11).…”
Section: Methodsmentioning
confidence: 99%
“…However, this kind of solvent mixture has been reported to have matrix effects on the signals of the analytes by interfering with the ionization process and causing a reduction of the accuracy (18). Given that the composition of e-cigarette liquids changes from product to product, the applicability of this method should be evaluated over a wide range of e-liquid compositions.…”
Section: Evaluation Of Matrix Effectsmentioning
confidence: 99%